1973
DOI: 10.1136/gut.14.10.794
|View full text |Cite
|
Sign up to set email alerts
|

Serum carcinoembryonic antigen in clinical disorders

Abstract: SUMMARY Carcinoembryonic antigen (CEA) levels have been measured in the serum of 490 patients and 93 normal controls using the double antibody radioimmunoassay technique. Levels were elevated in 71 of patients with carcinomata of the gastrointestinal tract and in 42% with other types of malignancy. In patients with non-neoplastic disease of the gastrointestinal tract and liver, elevated levels were found in 14 and 66 % respectively. In general the CEA level tends to be higher in cancer patients with haematogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…Here, we show that bsFab-dependent cytotoxicity is only slightly impacted by the concentration of soluble CEA exceeding concentrations found in the majority of patients with cancer (46). Thus, as already suggested by some clinical studies using anti-CEA antibodies (47,48), soluble CEA should not have a significant impact on the clinical efficacy of the bsAb.…”
Section: Discussionmentioning
confidence: 55%
“…Here, we show that bsFab-dependent cytotoxicity is only slightly impacted by the concentration of soluble CEA exceeding concentrations found in the majority of patients with cancer (46). Thus, as already suggested by some clinical studies using anti-CEA antibodies (47,48), soluble CEA should not have a significant impact on the clinical efficacy of the bsAb.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, the serum levels were in excess of 40 ng/ml in the majority (92%) of patients including those with localized disease. The levels are even greater than those in carcinomata ofthe gastrointestinal tract, bronchus and breast, in which serum CEA above this level is seen in only 12-13% of early and localized lesions and in 56-77% of distant metastases (Laurence et al, 1 972b;Booth et al, 1973). It may be ascribed to the high content of CEA in the tumour cells and also to abundant blood supply to the endocrine organ.…”
Section: Resultsmentioning
confidence: 97%
“…Shown in Table II (Dykes and King, 1972;Laurence et al, 1972a,b;Booth et al, 1973;Hansen et al, 1974 (Reynoso et al, 1972) and in about half the patients with the other 2 diseases (Dykes and King, 1972;Laurence and Neville, 1972a Early sporadic studies on thyroid diseases showed that a positive CEA result was found in only one out of 9 patients with thyroid carcinoma but in none of 8 patients with adenoma or nodular goitre (Laurence et al, 1972b;Reynoso et al, 1972;Booth et al, 1973). Quite recently Rochman et al (1975) reported a more frequent elevation of CEA in their series including 37 patients with thyroid carcinoma, but the positivity was statistically significant only in cases with no previous history of childhood irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…al., 1972;Booth et al, 1973). The upper limit of the normal range with this assay is 15 ng/ml, and the use of this test for measuring CEA in serum samples from lung-cancer patients has been reported previously Comparison of immunocytochemical anti-CEA localization with serum CEA levels is shown in Table II for the 86 patients for whom there were both preoperative and postoperative serum samples available for assay.…”
mentioning
confidence: 99%